Comparative Analysis In The Treatment Of Myocardial Infarcted Patients In The Tertiary Care Hospital Of Peshawar Against American Heart Association (ASA) Treatment Guidelines - Khan, Sher Afghan; Nawaz, Qadeer; Ahmad, Sameer; Khattak , Zainab; Khan, Sana; Munir, Attiya (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: To analyze pharmacotherapy provided in the hospital for MI indications and outcomes and to assess the protocols that are practiced for MI patients against the AHA and NICE guidelines. Methods: This study was conducted from 23rd July 2022 to 13th December 2022 in Cardiology ward of Lady Reading Hospital (LRH), Peshawar, Khyber Pakhtunkhwa, Pakistan. Patients of Myocardial Infarction (n = 240) admitted to hospital during the said period were included in this work. Results: The results showed that around 77% (185) of male patients suffered from MI as compared to 23% (55) of female patients. In our study only 68% of the patients were kept on aspirin and clopidogrel simultaneously, rest were either only administered aspirin or clopidogrel. The p-value for anti-coagulant and beta-blocker usage was found to be significant as it came out to be less than 0.001 whereas the use of ACE inhibitors was around 0.67, which stated that it was the least important. Conclusion: MI is as emergency that needs the patients follow up and monitoring and their treatment is administered to the latest and most advanced guidelines whether they are AHA or NICE guidelines. For this a thorough study was conducted on admitted patients in cardiac ward with MI and the drugs data was tabulated. Then studied the different internationally accepted guidelines that are followed by the most advanced hospital in the world ranging from Europe to America. The data collected showed that the tertiary care hospital of Peshawar do not follow the latest new guidelines. The practicing doctors administered the drugs that were correct almost half decade ago but now new guidelines have overtaken them which leads to improved patients morbidity and decreased mortality.